Dakwah Islam dan Karakter Da’i di Era Teknologi - Muhtar, Alvin Afif; Rohman, miftakhul; Mirwan Hariri, Muh. (SINDA: Comprehensive Journal of Islamic Social Studies, 2023)
This research is a qualitative type and was carried out using a documentation data collection method. The era of technology has provided challenges as well as great opportunities for a da'i in carrying out da'wah. It can be said that the challenges faced by previous and current preachers are very much different. However, the Qur'an as the main source for Islam is a book that is unique from the others. In his book, the Qur'an has regulated all aspects of life and provides solutions for every challenge of the times. Therefore, this study will describe the characteristics of da'i based on Islam to face the challenges of da'wah. There are three characteristics of a preacher according to Islam that researchers found and must be fulfilled by a preacher in the present. First, open to the development of science. Second, being a good role model in terms of worshiping God and relationships with others. Third, always be careful and wise in speaking.